Comparison of the effects of hexetidine and chlorhexidine mouthwash on the plaque index - Jeffrey, Jeffrey; Novamaura, Regyta; Meliawaty, Florence (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Plaque can cause damage to the tooth structure and supporting tissues, so it is necessary to take plaque control measures. The use of mouthwash such as hexetidine and chlorhexidine in chemical plaque control is effective in reducing plaque formation. Both of these mouthwashes were proven to have antibacterial activity against Streptococcus mutans which is one of the bacteria that causes plaque, so it is necessary to compare the effectiveness of the two ingredients to determine the difference in the effectiveness of the two types of mouthwash on the plaque index.Methods: This research method is a pre-test post-test control group design. The plaque index examination was carried out before and after gargling. The subjects in this study consisted of 32 students of state junior high school (SMPN) 2 Cimahi aged 13-15 years. This research was conducted by examining the Silness and Loe plaque index. Chi-square was used to test the normality of the data and then analyzed by t-test.Results: The results showed that there was a difference in the mean plaque index after rinsing with hexetidine and chlorhexidine of 0.077 and 0.167, respectively.Conclusion: There was a significant difference in the comparison of plaque index after gargling using hexetidine and chlorhexidine mouthwash, where hexetidine showed more effective results as an antibacterial agent in reducing plaque in the oral cavity.